The Effect of Pressure, Opportunity, Rationalization, Competence, and Arrogance on the Potential for Fraudulent Financial Reporting at PT Pegadaian, Medan - Awalina Febriani Lubis; Renny Maisyarah (Equivalent : Journal of Economic, Accounting and Management, 2026)
Fraudulent financial reporting remains a critical issue in the financial services sector, including state-owned enterprises, as it may undermine public trust and corporate governance quality. This study examines the effects of the Fraud Pentagon dimensions—pressure, opportunity, rationalization, competence, and arrogance—on the potential for fraudulent financial reporting at PT Pegadaian (Persero), Medan Branch. Primary data were collected using a Likert-scale questionnaire distributed to 65 finance and accounting employees using a census sampling technique. Data were analyzed using PLS-SEM (SmartPLS) by assessing the measurement model (validity and reliability) and the structural model (path significance) through bootstrapping. The results indicate that arrogance, competence, and opportunity have positive and significant effects on the potential for fraudulent financial reporting, while pressure and rationalization show positive but insignificant effects. The R² value of 0.284 suggests that the model explains 28.4% of the variance in fraudulent financial reporting potential. These findings imply that fraud prevention should prioritize strengthening internal controls to reduce opportunities, managing authorization/access related to perpetrators’ capabilities, and reinforcing ethical leadership and oversight to mitigate override tendencies associated with arrogance